2013
DOI: 10.1097/inf.0b013e3182a14407
|View full text |Cite
|
Sign up to set email alerts
|

Novel Inflammatory Markers, Clinical Risk Factors and Virus Type Associated With Severe Respiratory Syncytial Virus Infection

Abstract: Background Virus-induced inflammation contributes to respiratory syncytial virus (RSV) pathogenesis. We sought to determine the specific mediators that are associated with more severe illness in young children. Methods Children ≤ 5 yrs of age seen in our emergency department for respiratory symptoms from September 1998 to May 2008 were eligible for enrollment. Nasopharyngeal (NP) wash samples were collected from all eligible patients, and clinical data were recorded. Individuals were included in this study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
83
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 40 publications
4
83
1
2
Order By: Relevance
“…To answer the question whether a causal relationship exists between responsiveness of RIG-I-dependent antiviral immune signaling prior to RSV infection and outcomes of RSV infection, a population-based longitudinal (birth cohort) study is required, including a much larger cohort of children. Interestingly, a recent case-control study by Tabarani et al (49) had found that nasopharyngeal wash samples of children with moderate and severe RSV infection (i.e., requiring hospitalization, and intensive care unit stay, respectively) contained elevated levels of several cytokines (e.g., IL-6, IL-8, TNF-a, and IFN-a) when compared with NP samples from RSV-infected children with mild RSV infection (i.e., that did not require hospitalization). This finding suggests an association between increased, rather than decreased, innate immune responses and severity of illness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To answer the question whether a causal relationship exists between responsiveness of RIG-I-dependent antiviral immune signaling prior to RSV infection and outcomes of RSV infection, a population-based longitudinal (birth cohort) study is required, including a much larger cohort of children. Interestingly, a recent case-control study by Tabarani et al (49) had found that nasopharyngeal wash samples of children with moderate and severe RSV infection (i.e., requiring hospitalization, and intensive care unit stay, respectively) contained elevated levels of several cytokines (e.g., IL-6, IL-8, TNF-a, and IFN-a) when compared with NP samples from RSV-infected children with mild RSV infection (i.e., that did not require hospitalization). This finding suggests an association between increased, rather than decreased, innate immune responses and severity of illness.…”
Section: Discussionmentioning
confidence: 99%
“…The diverging results from this and our study may be explained by the different study design. The study by Tabarani et al (49) was designed to examine cytokine levels in the upper airways of patients presenting with natural infection, which is inevitably delayed until symptoms occur and disease is well advanced. Therefore, the findings may be a consequence of higher viral loads in patients with severe illness, as it had been suggested in previous studies (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies exist in the literature investigating the effect of inflammatory cytokines in patients with bronchiolitis, pneumonia, respiratory distress, asthma and isolated from specific respiratory virus pathogens [22][23][24][25] , no studies exist comparing the severity of croup and levels of cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In a large study conducted by Tabarani et al 22 , which investigated patients with RSVpositive lower respiratory infection, it was shown that a positive correlation existed between inflammatory cytokines and disease severity. Similar results were obtained in a study conducted by Diaz et al 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Vários estudos sugerem que o HRSV do grupo A está mais associado à doença severa, no entanto, esse ainda não é um ponto totalmente consensual Smyth et al, 2002;Tabarani et al, 2013). Postula-se também que há uma associação positiva entre o nível de replicação do vírus e a gravidade da doença (DeVincenzo et al, 2010).…”
unclassified